1994
DOI: 10.3109/00016489409126109
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Findings Associated with Chronic Noise Induced Hearing Impairment

Abstract: Histological and functional derangements of the vestibular system have been reported in laboratory animals exposed to high levels of noise. However, clinical series describe contradictory results with regard to vestibular disturbances in industrial workers and military personnel suffering from noise induced hearing loss (NIHL). The purpose of the present study was to evaluate vestibular function in a group of subjects with documented NIHL, employing electronystagmography (ENG) and the smooth harmonic accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 16 publications
1
34
0
2
Order By: Relevance
“…Golz et al had reported that noise results in asymmetrical or symmetrical hearing loss with abnormal vestibular functions. [2][3][4] Exposure to industrial solvents and noise can have an adverse effect on hearing and balance mechanisms in humans and animals. [5,6] Body sway increases in patients with noise-induced hearing loss (NIHL) suggesting sub-clinical disturbances of the vestibular system.…”
Section: Introductionmentioning
confidence: 99%
“…Golz et al had reported that noise results in asymmetrical or symmetrical hearing loss with abnormal vestibular functions. [2][3][4] Exposure to industrial solvents and noise can have an adverse effect on hearing and balance mechanisms in humans and animals. [5,6] Body sway increases in patients with noise-induced hearing loss (NIHL) suggesting sub-clinical disturbances of the vestibular system.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional VEMP test using 95 dB HL acoustic stimuli for 200 consecutive responses in 40 seconds will not cause temporary threshold shifts of the hearing. However, if higher intensity noise persists, both cochlea and saccule may be damaged because anatomical proximity of the saccule to the stapedial footplate points to the possibility of acoustic trauma associated with saccular dysfunction (8). Therefore, it was the authors' premise that abnormal VEMPs after acute acoustic trauma may be caused by saccular damage from very high intensity noise; consequently, irreversible HL ensued.…”
mentioning
confidence: 97%
“…Hence, intense sound and vibration can induce vestibular reflexes, whereas the vestibular fibers are also able to respond to sound (5,6). Accordingly, acoustically responsive saccular afferents trigger acoustic reflexes of the sternocleidomastoid (SCM) muscle, and measurement of such reflexes may reflect the saccular function (7,8).…”
mentioning
confidence: 99%
“…Early studies showed that the sacculus and the cochlea (pars inferior) can be affected by noise, whereas the utriculus and semicircular canal are not [2,3,13,14] . There is no postmortem study on the sacculus's involvement in NIHL.…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear damage caused by acoustic trauma usually results in hearing loss and tinnitus. Similar to the effects of acoustic trauma on the cochlea, some parts of the vestibular system, such as the sacculus, may also be affected [1,2] . In this circumstance, vestibular symptoms can appear but may be neglected [3,4] .…”
Section: Introductionmentioning
confidence: 99%